2013
DOI: 10.1016/j.jacc.2012.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Coronary Computed Tomography Angiography in the Emergency Department

Abstract: Compared with UC, the use of CCTA in the ED is associated with decreased ED cost and length of stay but increased ICA and revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(76 citation statements)
references
References 42 publications
5
70
1
Order By: Relevance
“…This was a single-center study but included patients similar to those reported in other multicenter trials comparing SPECT with CTA (3,4). Second, although our event rate was low, it was comparable to other studies evaluating patients with CTA (3.8 vs. 4.4%) (16). Third, most patients were not imaged in the ED but admitted under observational care because neither CTA nor SPECT was available in the evening hours.…”
Section: Cacssupporting
confidence: 60%
“…This was a single-center study but included patients similar to those reported in other multicenter trials comparing SPECT with CTA (3,4). Second, although our event rate was low, it was comparable to other studies evaluating patients with CTA (3.8 vs. 4.4%) (16). Third, most patients were not imaged in the ED but admitted under observational care because neither CTA nor SPECT was available in the evening hours.…”
Section: Cacssupporting
confidence: 60%
“…[11][12][13] Several recent randomized studies and two metaanalyses have been published examining the diagnostic utility of CTA in evaluating patients in the ED with possible ACS. [14][15][16][17][18][19] Recent CTA studies have suggested efficient triage of patients, safe expedited discharge from the ED, cost effectiveness, and lower radiation dose when compared to standard diagnostic evaluation including MPI. However, this comparison has been to older conventional Na-I SPECT cameras using traditional rest-stress protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the performance of CTA as the first test for chest pain evaluation 5, 6. The largest study on this subject was the PROMISE (The Prospective Multicenter Imaging Study for Evaluation of Chest Pain) trial 7.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also associated early CTA use with fewer heart attacks. Both meta‐analysis of stable angina patients5 and meta‐analysis of emergency room patients6 suggested a significantly lower incidence of myocardial infarction in those randomized to early CTA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation